Cone beam computed tomography: A diagnostic aid in rhinomaxillary mucormycosis following tooth extraction in patient with diabetes mellitus - Shilpa Padar Shastry; Padmashree Srinivas Murthy; T R Jyotsna; Naveen N Kumar (Wolters Kluwer Medknow Publications, 2020)
Mucormycosis is a fatal, opportunistic deep fungal infection caused by genera Rhizopus, and compromised systemic health of the patient predisposes to this condition. Rhino maxillary or rhino nasal form of mucormycosis begins after the inhalation of fungal spores and invasion into the nasal mucosa, and spreads to the paranasal sinuses. This infection can also extend into orbits and intracranium causing fatal rhino orbito-cerebral mucormycosis. Hence early intervention is very significant in terms of prognosis. The aim of current paper is to report a case of rhinomaxillary mucormycosis involving palate, nasal and maxillary sinus in an uncontrolled diabetic patient following tooth extraction highlighting the etiopathogenesis, spread of this infection and cone beam computed tomography (CBCT) features.